Happiness capital: resources for student wellbeing - Ziegler, Albert; Bakhiet, Salaheldin Farah Attallah; Issa, Ahmed Nabawy Abdou; Essa, Yossry Ahmed Sayed; Naujoks-Schober, Nick (Frontiers in Education, 2025)
This study explores a resource-based perspective on subjective wellbeing in educational contexts by introducing the concept of happiness capital. Building on the educational and learning capital approach, we adapted existing measures to assess how personal and environmental resources contribute to students’ wellbeing. In a sample of 1,528 Egyptian secondary school students, perceived happiness capital significantly predicted life satisfaction, positive and negative emotions across all age groups. These findings suggest that the same resource structures supporting learning can foster emotional flourishing. We briefly discuss implications for resource-based models of wellbeing in education and propose directions for future research.